Traditional Chinese Medicine as an Effective Complementary Non-Pharmacological Approach to Mild Cognitive Impairment: A Call for Collaboration - Klimova, Blanka; Kuca, Kamil; Valis, Martin; Hort, Jakub (Journal of Alzheimer's disease, 2019)
Currently, there is an increase in the number of older people worldwide. Unfortunately, this demographic trend causes a rise in aging diseases, one of which is dementia. Recent research studies have indicated that mild cognitive impairment (MCI) may serve as a predictor of dementia in many patients. At present, there is no pharmacological treatment against MCI. Therefore, there is constant search for novel alternative non-pharmacological approaches to improve MCI. One of the effective complementary emerging approaches seems to be Traditional Chinese Medicine (TCM), which is nowadays becoming quite popular in the treatment of different disorders. The purpose of this study is to explore the efficacy of TCM as an effective complementary non-pharmacological tool for the improvement and treatment of MCI in older adults. The methods used for this review study included a literature search in the world's databases: Web of Science, Scopus, PubMed, and Springer. Afterwards, methods of comparison and evaluation of the findings from the selected studies were applied. The results of this review study indicate that TCM might be a beneficial complementary non-pharmacological approach to the improvement and treatment of MCI in older individuals. Nevertheless, more rigorously designed quality randomized clinical trials should be conducted in order to conclusively prove efficacy of TCM on the improvement of MCI among older population groups. In addition, there is an urgent call for a functional collaboration between western and eastern medicinal approaches, which could contribute to the enhancement of the overall quality of life of these aging population groups.
Keywords: mild cognitive impairment; Traditional Chinese Medicine; Medicine, Chinese Traditional; Humans; collaboration; limitations; Complementary Therapies; lidé; Randomized Controlled Trials as Topic; Benefits; kognitivní dysfunkce; intervention; tradiční čínská medicína; older people; komplementární terapie; randomizované kontrolované studie jako téma; Cognitive Dysfunction